Structural Analysis and Biological Toxicity of Aflatoxins B1 and B2 Degradation Products Following Detoxification by Ocimum basilicum and Cassia fistula Aqueous Extracts - Iram, Wajiha; Anjum, Tehmina; Iqbal, Mazhar; Ghaffar, Abdul; Abbas, Mateen; Khan, Abdul Muqeet (Frontiers in Microbiology, 2016)
This study showed the comparison between Ocimum basilicum and Cassia fistula (leaves & branch) aqueous extracts for their ability to detoxify of aflatoxin B1 and B2 (AFB1; 100 µg L-1 and AFB2; 50 µg L-1) by In Vitro assays and decontamination studies. Results indicated that O. basilicum leaves extract was found to be highly significant (P < 0.05) in degrading AFB1 and AFB2 i.e. 90.4% and 88.6% respectively. However O. basilicum branch, C. fistula leaves and branch extracts proved to be less efficient in degrading these aflatoxins, under optimized conditions i.e., pH 8, temperature 30˚C and incubation period of 72h. Moreover the antifungal activity of these plants extracts were also tested. The findings depicted that O. basilicum leaves extract showed maximum growth inhibition of aflatoxigenic isolates i.e., 82 – 87% as compared to other tested plants extracts. The structural elucidation of degraded toxin products by LCMS/MS analysis showed that nine degraded products of AFB1 and AFB2 were formed. MS/MS spectra showed that most of the products were formed by the removal of double bond in the terminal furan ring and modification of lactone group indicating less toxicity as compared to parent compounds. Brine shrimps bioassay further confirmed the low toxicity of degraded products, showing that O. basilicum leaves extract can be used as an effective tool for the detoxification of aflatoxins.